Natural Law and Civilizational Progress: Assumptions of a Political Theory in Simonas Daukantas’s Historiography - Pivoras, Saulius (Politologija, 2019)
This article aims to identify and reconstruct a few main elements of political theory upon which the works of Simonas Daukantas, the founding father of the national Lithuanian written history, are based. Daukantas’s major works on Lithuanian history were researched while identifying and closely analyzing the passages where Daukantas specifically speaks about natural law and civilizational progress. Daukantas’s history works were considerably influenced by authors of Neostoic natural law theory, such as Hugo Grotius, Samuel Pufendorf, and Antoine-Yves Goguet. This influence shows in the adopted conceptions of natural needs, natural sociability, and a characterization of the emergence of private property rights in Lithuania with the help of conjectural history methods. Daukantas traces natural law elements in the oldest customs of the people and therefore gives most attention to reconstructing and describing the mores of the ancient Lithuanians. In describing historical evolution, he applied in his works the concepts of bright and dark periods as well as the distinctions of other separate stages of civilizational progress as discussed in Enlightenment historiography and conjectural history in particular.